(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Age determination is one of the most important parameters for human identification. Radiographic changes during epiphyseal union provide an important means to estimate the age of adolescent and young adult skeletons. This study aims to investigate the relationship between stage of epiphyseal union at the wrist joint and chronological age in Chhattisgarh population (Central India). The study was carried out in a total of 100 healthy subjects (40 girls and 60 boys) aging from 13 to 20 years. The obtained results from the radiographs enrolled in the current study revealed that the complete epiphyseal union around wrist joint is seen at 18-19 years in males & 17-18 years in females. Females were consistently developing epiphyseal union at a younger age than their male counterparts, with a two years difference. The results suggested that the ages of epiphyseal union are found to vary greatly all over the world indicating the need for separate standards of age of epiphyseal union for separate regions.